2013
DOI: 10.4067/s0718-090x2013000200004
|View full text |Cite
|
Sign up to set email alerts
|

IDENTITY AND lNSTITUTIONALISATION AS TRUST BUILDING STRATEGIES: THE SINO-CHILEAN CASE

Abstract: * this paper has been possible thanks to the following institutions: the alßan Programme: "high level scholarships to Latin america nº e07d400981cL", universities' china committee in London (uccL) and vicerrectoría de investigación. pontificia universidad católica de chile, Fondos inicio/nº 7/2012. i would like to thank the anonymous reviewers that helped me to improve this paper. i sincerely appreciate their comments and advice. i also want to thank my colleagues ingrid Bachman and sebastian valenzuela who ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Currently, around 400 Chilean firms keep steady commercial relations with China, mostly in the mining, forestry, wine and agricultural sector. As previously stated (Labarca, 2014), this leaves Chilean firms in a state of asymmetry regarding their counterparts, not only in the degree of interest shown by each part, but also in market size, business opportunities and negotiation capacity (Labarca, 2012).…”
Section: Case Studymentioning
confidence: 91%
See 1 more Smart Citation
“…Currently, around 400 Chilean firms keep steady commercial relations with China, mostly in the mining, forestry, wine and agricultural sector. As previously stated (Labarca, 2014), this leaves Chilean firms in a state of asymmetry regarding their counterparts, not only in the degree of interest shown by each part, but also in market size, business opportunities and negotiation capacity (Labarca, 2012).…”
Section: Case Studymentioning
confidence: 91%
“…These collection techniques were appropriate to answer the research question, insofar we needed knowledgeable and experienced executives and with high degree of involvement in the subject. As previous research on the subject has shown (Labarca, 2012), the key informants for this case study are usually those who are in direct contact with their business counterparts such as general managers, business managers or communications managers. Therefore, the potential informants were contacted in relation to their knowledge and experience with trade partners.…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years, China has become increasingly more concerned with its international image, investing in its public diplomacy and crafting careful messages to set not only its position toward Latin America but to frame particular messages to build trust (Labarca, 2013). China's White Papers (2008Papers ( , 2016, as well as the actions and words of Chinese diplomats in Latin America, frame China's public diplomacy narratives between Latin America and Chile.…”
Section: Narratives In Public Diplomacy: China and Its Presence In Chilementioning
confidence: 99%
“…This narrative has been functional to the Sino-Chilean diplomatic rhetoric in which economic cooperation and friendship act as the engine of bilateral relations within a comfortable interplay with governmental authorities and Chinese media rhetoric (Bernal-Meza, 2016;Labarca & Montt Strabucchi, 2019;República Popular China, 2008, 2016. Furthermore, many have argued that Chile is an interesting case study for understanding the Chinese geopolitical and economic strategy towards Latin America (Gachúz, 2012) since Chile may work as a demonstration of Beijing's benign influence in the region (Labarca, 2013). While this article focuses on elites as political actors and not on the state, following Zhu and Wang (2018), we believe that the examination of editorials and opinion columns allows for the understanding of the attitudes of a country's elite class and/or government towards Chinese presence in the region.…”
Section: Narratives In Public Diplomacy: China and Its Presence In Chilementioning
confidence: 99%
“…Existen diversas conceptualizaciones sobre qué es confianza, dependiendo de si se enmarcan en el institucionalismo, el culturalismo o las teorías de la elección racional (Labarca 2013;Kim 2005). En este trabajo, entendemos la confianza como la creencia de que otros no nos dañarán deliberadamente o con conocimiento si es que pueden evitarlo, y que cuidarán nuestros intereses en la medida de lo posible (Newton 2007: 343).…”
Section: Política: Definición Y Antecedentesunclassified